DAN BATANG PISANG TERHADAP KONSUMSI DAN KECERNAAN SERAT KASAR, KONSENTRASI VOLLATILE FATTY ACID DAN GLUKOSA DARAH PADA KAMBING KACANG (Effect of complete feed fermented gliciridia sepium fallen leaf and banana pseudo stem to intake and digestibility....) - Angga Dwi Firmanto; Erna Hartati; Gusti Ayu Yudiwati Lestari (Universitas Nusa Cendana, 2020)
The purpose of this study was to determine the effect of providing fermented gliciridia fallen leaf and banana stem in complete feed with different level on crude fiber intake and digestibility, intake of digestible crude fiber, VFA concentration and blood glucose levels of kacang goat. This study used 4 male goats with age under one year, average body weight of 10.5 kg. The research used latin square design with 4 periods and 4 treatments, which consisted of P70S0, P40S30, P30S40, P0S70. The parameters observed were crude fiber intake and digestibility, intake of digestible crude fiber, VFA concentration and blood glucose levels. The results showed that the provision of complete gliciridia fallen leaf and banana stems with different level had no significant difference (P> 0.05) on crude fiber intake and digestibility, ingested digestive fiber consumption, blood glucose concentrations. However, feeding goats with a complete feed of gliciridia fallen leaf and banana stems with different levels had significantly increased ​​(P <0.01) VFA concentration. Therefore, it can be concluded that providing goats with fermented complete feed of gliciridia fallen leaf and banana stem did not increase the value of crude fiber consumption and digestibility, consumption of undigested crude fiber and blood glucose levels but was able to increase VFA concentration